Crack cronology of reinforced concrete beam under impact loads - Mohd Jaini, Zainorizuan (2008)
Impact is one of dynamic transient loadings which is contribute to structure damages such as cracks and frequently generate a dangerous effect to reinforced concrete structures. Nowadays, several areas of civil engineering incorporate the need to be able to predict such structural behaviour under impact loading. Previous researchers have noted that concrete structures under impact loading show different behaviour from that under static loading. This study presents a three-dimensional nonlinear finite element simulation of the reinforced concrete beams subjected lowvelocity impact loading. The main objective of this study is to determine the crack chronology specifically in time and location. Beam with geometry 1.5m long, 0.2m depth and 0.1m width has been modelled by ELFEN. Numerical modelling and ELFEN code is based on previous study of the reinforced concrete beam under impact loading conducted by P.J. Thiele (2005). This study has involved 16 models which are divided into three factors of simulation, that are modelling factors to determine the most suitable model, support conditions to study crack chronology caused by the rigid support, support material and support thickness, and impactor factors to determine the crack chronology caused by various velocities and densities. From the results, the main crack modes are spalling crack at the top surface of beam and scabbing crack on the bottom surface of beam. It is found in this study that there are two categories of crack chronologies. First is crack happens at the bottom surface of beam recognized as scabbing crack and then followed by the beam crack at the support area and finally spallation crack. Another category of crack chronology is occurs as scabbing crack, then spallation crack and finally beam crack at the support area. Cracks due to impact loading can be described by wave theory. Scabbing crack caused by the direct impact wave and compression condition at the rare area of beam. Spallation crack occurs by two reasons, the impact wave propagate to the support area and the rarefaction wave that reflected from support. Besides that, spallation crack also occur related to its global deformation. For the purpose of validation, the results obtained from numerical simulation of the threedimensional reinforced concrete beam, which is carried out using the finite element software ELFEN are validated by deeply literature review. There are no comparisons between experimental results. Final cracks pattern for each model is carried out to make comparison with previous study of crack behaviour where the results are obviously similar. ii